Factors impacting gas content measurements using gas desorption by drilling underground boreholes - Zenghua Li; Qiangqiang Qi; Yongliang Yang; Yinbo Zhou; Bin Wang (Adsorption Science & Technology)
Accurate determination of the gas content in coalbeds is important for safe mining. Currently, gas desorption by drilling underground boreholes is the most commonly used gas determination method. However, this method is not very accurate and needs to be improved. In this study, we established a laboratory protocol based on coal adsorption studies to analyse factors affecting the measurement accuracy. The results showed that exposure time, sampling method, sample weight, particle size and gas loss estimate significantly affected the gas content measurement using gas desorption by drilling underground boreholes. Longer exposure time and increased particle size resulted in higher relative errors. Sampling by coring is more accurate than sampling by drilling. The higher the sample weight is for samples weighing less than 240 g, the larger the error of the in situ measurements of desorbed gas, residual gas and lost gas is. The error tends to stabilize for heavier samples. The gas losses at different exposure times calculated using the commonly used Barrer model, power function method and negative exponent method were compared. The gas loss error within 0–12 min, computed with the Barrer model, and after 12 min, computed with the power function method, is minimal. The modified formula of gas loss was obtained using the combination of a fitting analysis and the relationship between gas loss and exposure time. Subsequently, the optimal procedure for in situ gas content measurements using gas desorption by drilling underground boreholes was determined. The gas content errors for anthracite, gas coal, lean coal and long flame coal, which were measured using gas desorption by drilling underground boreholes and corrected using the gas loss formula, decreased significantly to less than 10%, thus, meeting the engineering accuracy norm.